A new perspective on GCRT J1745-3009 - Spreeuw, H.; Scheers, B.; Braun, R.; Wijers, R.; Miller-Jones, James; Stappers, B.; Fender, R. (EDP Sciences, 2009)
Context: Reports on a transient source about 1.25° south of the Galactic Centre motivated these follow-up observations with the WSRT and the reinvestigation of archival VLA data. The source GCRT J1745-3009 was detected during a 2002 Galactic Centre monitoring programme with the VLA at 92 cm by five powerful 10-min bursts with a 77-min recurrence while apparently lacking any interburst emission.Aims: The WSRT observations were performed and archival VLA data reduced to detect GCRT J1745-3009 again at different epochs and frequencies, to constrain its distance, and to determine its nature. We attempted to extract a more accurate lightcurve from the discovery dataset of GCRT J1745-3009 to rule out some of the models that have been suggested. We also investigated the transient behaviour of a nearby source.Methods: The WSRT data were taken in the “maxi-short” configuration, using 10 s integrations, on 2005 March 24 at 92 cm and on 2005 May 14/15 at 21 cm. Five of the six VLA observations we reduced are the oldest of this field in this band.Results: GCRT J1745-3009 was not redetected. With the WSRT we reached an rms sensitivity of 0.21 mJy beam-1 at 21 cm and 3.7 mJy beam-1 at 92 cm. Reanalysis of the discovery observation data resulted in a more accurate and more complete lightcurve. The five bursts appear to have the same shape: a steep rise, a more gradual brightening, and a steep decay. We found variations in burst duration of order ?3%. We improved the accuracy of the recurrence period of the bursts by an order of magnitude: 77.012 ± 0.021 min. We found no evidence of aperiodicity. We derived a very steep spectral index: a=-6.5 ± 3.4. We improved the 5s upper limits for interburst emission and fractional circular polarisation to 31 mJy beam-1 and 8%, respectively. Any transient behaviour of a nearby source could not be established.Conclusions: Models that predict symmetric bursts can be ruled out, but rotating systems are favoured, because their periodicity is precise. Scattering constraints imply that GCRT J1745-3009 cannot be located far beyond the GC. If this source is an incoherent emitter and not moving at a relativistic velocity, it must be closer than 14 pc.